Evaluation of Nurses’ Knowledge about Substance Abuse at Psychiatric Teaching Hospitals in Baghdad City - abbas, ihab; aljubori, ali (Iraqi National Journal of Nursing Specialties, 2017)
Objectives: To evaluate levels of nurses’ knowledge about substance abuse at psychiatric teaching hospitals in Baghdad city. Methodology: A descriptive analytical study conducts to meet study objectives during the period from 1-11-2014 To 10-5-2015 The study conduct at 4 teaching hospitals in three department (Baghdad Al Rusafa ,Al Karkh, Medical city) they includ Baghdad teaching hospital, Al Rashad teaching hospital, Ibn Rshud teaching hospital , and Al Kadhumeeain teaching hospital which select according to the study. A random sample of 100 nurses are working in teaching psychiatric hospitals , Al Rashad (60), Ibn Rshud (20) Baghdad teaching hospital (10) and Al Kadhumeeain (10) , A questionnaire is construct for the purpose of the study. consist of 58 items which are distribute in two part, A – general information which consist from 8 items, B- Nurses Evaluation of Knowledge about substance abuse which consist from 50 items..Data analysis through uses of program SPSS version 20 by application the following :Descriptive statistical data analysis approach: by use the following measurements: Frequencies. Percentages. Statistical table. Inferential: through the application of the Chi –square test This test use for determine the association between the nurse ’ demographic characteristics and the Evaluation Nurse knowledge about substance abuse. Results: The study founds 69% of the sample are male . 71% of them that are married ,40% 30-39 years old age ,78% ≤ 9 years career ,49% not enough monthly income. There are 57% have good level knowledge about smoking 41% have good level knowledge about alcohol There are 42% have weak level knowledge about drugs, There are asignificant association between knowledge smoking and marital status and There are significant association between knowledge smoking and level of education . Recommendations: recommend it, Increase implementation educational programs , Support nurses training about substance abuse specially drug abuse due to important of substance and Encourage researches about substance abuse